2019
DOI: 10.1002/ece3.5930
|View full text |Cite
|
Sign up to set email alerts
|

Will the climate of plant origins influence the chemical profiles of cuticular waxes on leaves of Leymus chinensis in a common garden experiment?

Abstract: Cuticular wax covering the leaf surface plays important roles in protecting plants from biotic and abiotic stresses. Understanding the way in which plant leaf cuticles reflect their growing environment could give an insight into plant resilience to future climate change. Here, we analyzed the variations of cuticular waxes among 59 populations of Leymus chinensis in a common garden experiment, aiming to verify how environmental conditions influence the chemical profiles of cuticular waxes. In total, eight cutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…However, no significant correlation between climate factors and the wax characteristics could be observed (data not shown). This was inconsistent with the results from L. chinensis where latitude, arid index, and the precipitation had been shown to be the most important climate parameters contributing to the variations of the total wax coverage and the amount of wax compositions (Li et al, 2020). In a common garden experiment of L. chinensis, rhizomes were collected from their field-growing environments and transplanted.…”
Section: Variations Of Cuticular Waxes Among Populations Were Induced By Their Original Environmentscontrasting
confidence: 67%
See 2 more Smart Citations
“…However, no significant correlation between climate factors and the wax characteristics could be observed (data not shown). This was inconsistent with the results from L. chinensis where latitude, arid index, and the precipitation had been shown to be the most important climate parameters contributing to the variations of the total wax coverage and the amount of wax compositions (Li et al, 2020). In a common garden experiment of L. chinensis, rhizomes were collected from their field-growing environments and transplanted.…”
Section: Variations Of Cuticular Waxes Among Populations Were Induced By Their Original Environmentscontrasting
confidence: 67%
“…Similar CV was also observed for the amounts of alkanes, primary alcohols, and aldehydes. A study on 59 populations of L. chinensis in a common garden experiment has also shown that great intraspecific trait variations were observed for total wax coverage and wax compositions (Li et al, 2020). Andrae et al (2019) also reported that M. quinquenervia had evolved their specific wax characteristics to adapt to their surroundings.…”
Section: Variations Of Cuticular Waxes Among Populations Were Induced By Their Original Environmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to its major role in stress response and adaptation, the cuticle is thought to play essential functions in plant interactions with the environment 26 . Additionally, the content and composition of cuticular wax vary greatly not only in different species but also under different environmental conditions, such as UV-B radiation, temperature and water conditions 27 .…”
Section: Discussionmentioning
confidence: 99%
“…latitude, elevation, illumination and aridity ( Hoffmann et al 2013 , Mitić et al 2016 , Feakins et al 2016 , Lykholat et al 2018 , Teunissen van Manen et al 2019 ). Wax biosynthesis is well-known for its plasticity, but some studies suggest that it may also result from heritable factors linked with the geographic origin and the environmental conditions of forest trees ( Mitić et al 2016 , Li et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%